Advancing gender equality in media industries: an innovative european approach - Padovani, Claudia; Ross, Karen (INTER DISCIPLINA, 2018)
Most people recognise that mainstream media industries are important players in contemporary societies, simultaneously galvanizing change through cutting-edge programming and technological development but also reinforcing long-standing inequalities and discrimination through the perpetuation of stereotypes in content and restricting career opportunities. When we consider the specific issue of gender and media and their inter-relationship, numerous research studies over the past 50 years have demonstrated persistent problems in terms of disrespectful representations of women, routine inequalities within the workplace and unequal gendered power relations in management structures (Tuchman et al., 1975; Gallagher 1995; Rush et al., 2005; Byerly 2011; North, 2015; Ross & Padovani, 2016). These issues serve to constrain societal progress and make the goal of gender justice extremely hard to achieve.